2013
DOI: 10.3892/ol.2013.1641
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p-Akt in ovarian serous carcinoma and its association with proliferation and apoptosis

Abstract: The aim of the present study was to determine the expression of p-Akt in ovarian serous carcinoma (OSC) and its association with proliferation and apoptosis. Paraffin-embedded tissues of patients aged between 35 and 64 years old without history of radiotherapy, chemotherapy and hormone therapy prior to surgery were collected. In total, samples included 12 ovarian serous cystadenomas (OSAs), 18 ovarian serous borderline tumors (OS-BTs) and 46 OSCs. Of the 46 OSC samples, 16 were well-differentiated, 20 were mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The PI3K/AKT/ GSK3β signaling pathway is one of the important signal transduction pathways, playing an anti-apoptosis and survival-promoting role in cells by activating a variety of downstream effector molecules [30]. Some studies showed that the signaling pathway is closely related to the occurrence and development of a variety of common malignant tumors, as the expressions of p-AKT and p-GSK3β are significantly higher than those in normal tissues within tumors like glioma, ovarian carcinoma, and breast carcinoma [31][32][33][34]. Hongen Lei et al showed that LF-MF decreased human prostatic adenocarcinoma cell proliferation and the activity of AKT pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/ GSK3β signaling pathway is one of the important signal transduction pathways, playing an anti-apoptosis and survival-promoting role in cells by activating a variety of downstream effector molecules [30]. Some studies showed that the signaling pathway is closely related to the occurrence and development of a variety of common malignant tumors, as the expressions of p-AKT and p-GSK3β are significantly higher than those in normal tissues within tumors like glioma, ovarian carcinoma, and breast carcinoma [31][32][33][34]. Hongen Lei et al showed that LF-MF decreased human prostatic adenocarcinoma cell proliferation and the activity of AKT pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…AKT has direct effects on the effectors of the apoptotic pathway, including Bcl-2 (38). Bcl-2 activity is regulated via p-AKT in various cell types (39). AKT phosphorylates Bax, disrupting its interaction with Bcl-XL to protect cells from apoptosis (40).…”
Section: Discussionmentioning
confidence: 99%